The Transformation of The Information Wave Into Virtual Civilization and the Ethical Questions It Raises. - Targowski, Andrew (Comparative Civilizations Review)
The purpose of this investigation is to define the main contents and issues of the impact of informing systems on the rise and development of Virtual Civilization. The methodology is based on an interdisciplinary big-picture view of the elements of development of virtual civilization and their interdependency. Among the findings are the following: Virtual Civilization has infrastructural characteristics, a world-wide unlimited, socially constructed work and leisure space in cyberspace, and it can last centuries/millennia--as long as informing systems are operational. Practical implications: The mission of Virtual Civilization is to control the public policies of real civilizations in order to secure the common good in real societies. Social implications: The quest for the common good by virtual society may limit or even replace representative democracy by direct democracy which, while solving some problems in a positive way, may eventually trigger permanent political chaos in real civilizations. Originality: This investigation defines the question of ethics regarding the role of informing systems in the development of Virtual Civilization by providing an interdisciplinary and civilizational approach at the big-picture level.